Does Antithrombotic Drug Use Mandate Trauma Team Activation in Awake Geriatric Patients with Intracranial Hemorrhage?. Issue 7 (July 2018) - Moyer, Jeffrey A.; Shah, Jharna; Nowakowski, Kevin; Martin, Anthony; McNicholas, Amanda; Muller, Alison; Fernandez, Forrest B.; Ong, Adrian W.
Antithrombotic (anticoagulant [AC] and antiplatelet [AP]) drugs have been associated with mortality in geriatric patients with intracranial hemorrhage (ICH). It is unclear whether trauma team activation (TTA) in this cohort impacts outcome. Patients ≥65 years with a Glasgow Coma Scale of ≥13 and ICH over four years were included and were divided into three groups according to type of drug: group 1, AC with or without AP; group 2, AP only and; group 3, no AC or AP. The Rotterdam score was used to characterize the severity of CT findings. The primary outcome was inhospital mortality or transition to comfort measures. The secondary outcome was need for neurosurgical intervention within 48 hours. Logistic regression analysis was performed to evaluate for predictors of each outcome. Of 419 patients, 20.5, 50.4, and 29.1 per cent belonged to groups 1, 2, and 3, respectively, with TTA occurring in 39.5, 18.0, and 32.0 per cent of the respective groups. Within each group, there were no differences for the primary and secondary outcomes whether or not TTA was triggered. TTA patients had shorter times to CT (median, 20 minutes versus 80 minutes, P < 0.0001) and to administration of reversal agents (median, 105 minutes versus 255 minutes, P < 0.0001). Age, head-Abbreviated Injury Score, and the Rotterdam score were predictors for both outcomes by multivariable analysis, whereas antithrombotic drug use and TTA were not. In awake elderly patients on antithrombotic drugs found to have ICH, TTA expedited evaluation and treatment but was not associated with mortality benefit.